An overview of beach soccer, sepak takraw and the application of machine learning in team sports - Rabiu Muazu, Musa; Anwar, P. P. Abdul Majeed; Norlaila Azura, Kosni; Mohamad Razali, Abdullah (Springer, 2020)
This chapter shall provide an overview of the sport of beach soccer as well as sepak takraw. It then provides a brief review on existing literature that employs machine learning on team sports. The clustering techniques, as well as machine learning models that are used in the book, are also deliberated. The participants (subjects) and the performance measures utilised in the study are also reflected in this chapter.